Pelaksanaan Pembelajaran Bahasa Indonesia: Studi Kasus di SMP Negeri 01 Kabun - Lestaria, Beta; Mukhlis, Muhammad (UIR Press, 2024)
The central component of education is the learning process, which includes a variety of components such as the curriculum, instructors, and learning theories. The purpose of this study is to explain and detail how Indonesian language instruction is being implemented at SMP Negeri 01 Kabun. Descriptive qualitative research methodology is used, with an emphasis on the opening, core, and closing stages of the learning process activities. Techniques for gathering data include documentation, questionnaires, and observation. The data analysis method includes forming conclusions, displaying the data, and reducing the data. The findings show that media and other learning tools have not yet been properly utilized in the implementation of Indonesian language learning at SMP Negeri 01 Kabun, which has resulted in less participatory and engaging learning experiences. This study emphasizes how crucial it is to keep assessing and refining instructional strategies in order to raise the standard of instruction at the institution.